Biochemical and heart adaptations to physical training and supplementation with amino acids - Dorofeeva, E. E.; Dorofeev, A. E. (The Journal of Strength and Conditioning Research, 2004)
This study evaluated the role of amino acids supplementation on the heart's adaptation under extensive training conditions. Sixty active athletes (bicyclists and swimmers) were separated into 2 groups: 30 were given amino acid mixture (1 g per 10 kg of body weight) for a period of 1 month, and the other 30 were given placebo for the same duration (control group). In the same time period, 20 subjects of similar age not engaged in physical training or sports activities were used as the additional control group. Blood concentrations of alanine transaminase (ALT), asparagine transaminase, lactate dehydrogenase (LDH), gamma-glutamil transpeptidase, alkaline phosphatase (ALP), amylase, triglycerides, albumin, interleukin-6 (IL-6), and interleukin-10 (IL-10) were determined for all subjects before and after the intervention period. Concentrations of LDH and ALP were increased, but concentrations of ALT, albumin, and triglycerides were decreased in the blood of trained athletes compared with healthy subjects not engaged in sports activities. In the athletes, some increases in IL-6 levels were noted; however, they were significantly (p < 0.05) lower than in patients with myocardiodystrophy. The values of IL-10 in athletes were higher than concentrations of IL-10 in patients with myocardiodystrophy but still lower than the normal values. The inhibition of IL-10 in blood may play an important role in the induction of apoptosis in cells of the heart muscle. After amino acid supplementation, the athletes' values for albumin, triglycerides, IL-10, LDH, and ALP were significantly increased compared with the post-placebo control groups. Enzyme activities of other enzymes remained unchanged in all groups. Histological data from a secondary study of actual heart tissue showed that the amino acids supplementation may have inhibiting effects on myocardial apoptosis. The criteria of efficiency of the amino acids supplementation were defined by the albumin, IL-6, and IL-10 concentrations.